Virtual flows and decoupling effects of water-carbon footprints in China’s ICT sector: analysis based on multi-regional input-output and decoupling models - Yao, Liming; Xu, Dongyu; Qian, Weijin (Frontiers in Environmental Science, 2025)
Driven by the digital economy, China’s Information and Communication Technology (ICT) industry has significantly intensified water and carbon pressures. By employing the Environmentally Extended Multi-Regional Input-Output (EE-MRIO) model in conjunction with the Tapio decoupling model and Structural Decomposition Analysis (SDA), this study quantifies interprovincial virtual water-carbon flows and their economic-environmental coupling from 2012 to 2017. The findings reveal a spatial imbalance characterized by “eastern agglomeration–western burden”, as well as a transition from unidirectional outflows to hub-based resource interactions. Decoupling trajectories exhibit regional variations: Jiangsu has achieved strong decoupling, Beijing remains heavily coupled, while Jiangxi and Yunnan demonstrate significant water decoupling. The SDA results indicate that structural expansion continues to be the primary driver: from 2012 to 2017, per capita demand contributed +2.06 and final demand structure +0.54 to the average growth in carbon footprint. Regarding the water footprint, the final demand structure contributed +0.085. Although reductions in intensity have provided localized mitigation, the persistence of structural pressures suggests that path dependence has not been entirely overcome. This study expands the analytical framework for measuring environmental footprints and decoupling within the ICT industry, providing valuable insights for decision-making towards regional green transformation and ecological responsibility reconstruction.